Digital Human Resource Management - Sharon S., Deborah; Aggarwal, Vaneeta (Gyan Management Journal, 2017)
The current period we are in, is the ’digital age’. The world altogether has undergone various changes with respect to economical, cultural and societal arenas. This generation (Millennials / Net Generation) of people has technology at their fingertips. This results in the workplace behavior and how they are taken care of in the organization. The management of human resources changes with change in technology. Usage of technology is prevalent in planning and implementation of various activities of HRM. HRM should change in relation to the environment and this affects the way it operates. The plans, policies, rules and regulations change. The major focus on dealing with digital HRM is that we have to address digital employees doing the digital work and managing using digital technologies. This paper focuses on the changes and challenges that happen when HRM goes digital. To understand the changes and challenges in digital HRM, this paper delineates the various dimensions or focus areas of digital HRM that is about ’Digital Employees: ’Digital Work’ and ’Digital Employee Management’. Human Resource Management is everything that is done with planning, organizing, coordinating, directing and controlling the human resources in the organization. All the systems and functions of human resource management undergoes change when it goes digital. Acquiring talent, Orienting the new employees Onboarding), Performance Management, Learning, Leadership Development, Communication, Impact of Social Media on the organization are some of the challenges an organization faces when digitalization happens in the workplace.